KINERJA ESG PADA PERUSAHAAN KELUARGA: PERAN FOUNDER DOMINATION, RISIKO PERUSAHAAN DAN KEPEMILIKAN INSTITUSIONAL - Yane Devi Anna; Feby Astrid Kesaulya (Universitas Swadaya Gunung Jati, 2026)
This study analyzes the effect of founder domination and firm risk on Environmental, Social, and Governance (ESG) performance, and examines the role of institutional ownership as a moderating variable. The research was conducted on family firms in the Indonesian manufacturing sector with a total sample of 83 companies observed over two years. Data were analyzed using moderated regression analysis. The results show that founder domination does not affect ESG performance, reflecting the diminishing influence of founders as control shifts to subsequent generations. Firm risk has a significant positive impact on ESG performance, suggesting that companies facing higher risk tend to strengthen their sustainability practices to enhance legitimacy and transparency. Institutional ownership is found to moderate the relationships between founder domination, firm risk, and ESG performance, confirming its role as an external governance mechanism that enhances monitoring quality and promotes more substantial sustainability commitments. These findings enrich the literature on family firms and ESG, particularly regarding the importance of ownership structure in shaping sustainability outcomes. Furthermore, the study confirms that improving ESG performance is not merely a compliance activity but an effective strategic response to the risks companies face. Keywords: Corporate Risk; ESG Performance; Founder Domination; Institutional Ownership.